INVENTARISASI INSTITUSI ADAT REJANG DALAM RANGKA PENYUSUNAN KOMPILASI HUKUM ADAT REJANG - Herlambang, Herlambang; Abdi, Muhammad; Harjanto, Andry; Yamani, Muhammad (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The research aims at finding values, principles, and norms of customary law in Indonesia that are necessary to improve the concept of rule of law in Indonesia. One of the customary laws that still exists in Indonesia is Rejang customary law (Hukum Adat Rejang) which applies in Rejang society, Bengkulu Province. The existence of Hukum Adat Rejang as customary law is influenced by values of kinship, community groupings and pattern of traditional Rejang tribes. In order to find and identify such norms, a legal anthropological research with a qualitative research would be used. The research was conducted at the District of Rejang Lebong, Lebong, and Kepahyang. The result of the research shows that kinship system of Rejang is based on patrilineal or matrilineal system. Rejang tribes consist of four tribes, they are Petulai Tubeui or Tubai, Petulai Bemani or Bermani, Petulai Jekalang or Jurukalang, Petulai Selupue or Selupu. There are some norms that could be identified in Rejang customary law, namely Bemaling, Menebo, Tikam, Sigar Kulit, Cucuk Kulit, Mea Bayang Daleak, Iram Coa Badaleak, Iram Badaleak, Tukak Takek Kukuk, Membalew, Cido Celako, Kejujung Tenggak, Mendaur Tenggak, Samun, Upet, Dawa, Sumbang, Johong Permayo, Mbut, Tambang, Pascas Poncong, Tepeket, dan Kerineak.Key words: Rejang customary law, institution of adat Rejang, compilation of adat Rejang